Short-term success of former dual enrolled career and technical education students at College of the Desert - Struwe, Kurt (Kansas State University, 2021)
This study explores the associations among community college student perceptions and short-term success in college. Guiding the study are two research questions: (1) what is the association between participation in dual enrollment and subsequent college success for CTE students formerly enrolled in dual credit secondary programs and those who were not, and (2) how do CTE students’ perceptions of their college experiences differ between CTE students formerly enrolled in dual credit secondary programs and those who were not enrolled in those programs? Study participants were students who were formerly enrolled in dual credit programs at the secondary school and those who were not. Previous literature indicates that students who participate in career and technical education (CTE) programs offered in high school are more motivated and successful in college CTE programs than those who were not. Dual enrollment isn’t only for high-achieving students; it also can benefit first-generation students, minority students, and low-income students. This study examined associations among variables in the intervention and comparison groups. Data were gathered from an online survey and the Student Information System (SIS) at College of the Desert to examine students’ experiences, perspectives, and motivation in college. These data were then analyzed using chi-square and t-test analyses. The intervention group had higher course completion rates than the comparison group, the only statistically significant difference among all associations that were tested. The intervention group had higher rates of intention to transfer to a four-year college than the comparison group but these differences were only marginally significant. Differences in low-income status and first-generation status were observed between the intervention and comparison groups but these differences also were only marginally significant.
Keywords: Dual credit; Success in college; Early college; College readiness; Career and technical education; Dual enrollment